Development of bacteria-based bioorganic phosphate fertilizer enriched with rock phosphate for sustainable wheat production - Aslam, Zoya; Yahya, Mahreen; Hussain, Hafiz Shahid; Tabbasum, Saira; Jalaluddin, Sabahet; Khaliq, Shazia; Yasmin, Sumera (Frontiers in Microbiology, 2024)
Please find enclosed our manuscript entitled as "Development of Bacteria-based Bioorganic Phosphate Fertilizer Enriched with Rock Phosphate for Sustainable Wheat Production" by Zoya et al., which we like to submit for publication as a research paper. We tried our level best to maintain the high quality that is testament of this journal.Wheat (Triticum aestivum L.) is the major staple crop for an estimated 35% world population. Adequate phosphorus (P) nutrition is critical for proper growth of wheat plant. But, there is imminent threat of P-limitation as P deposits had been overlooked in the past which will theoretically last for the next 600 years of global P supply. Overuse of synthetic agrochemicals for enhancing crop productivity has deteriorated the biological and physicochemical health of the arable soil, leading to a declining trend in agricultural productivity across the globe. Therefore, Phosphate solubilizing bacteria are ecofriendly alternative to chemical fertilizers that transform insoluble P compounds into available forms for plant uptake and a way to recover the soil fertility without environmental threats.Novel aspects/results from our study are:We aimed to design bioorganic Phosphate Fertilizer that deployed multifaceted PSB and organic amendments based on agro-industrial by-products to improve wheat growth and yield under P deficient conditions. This is the first comprehensive research work in which we use PSB and industrial by product based organic matter to release phosphorus from recalcitrant P forms i.e., rock phosphate. The successful bioorganic phosphate developed in this study extended the shelf life of highly efficient rhizosphere-competent P-solubilizers, that are competitive against the native bacteria, ultimately led to the improved wheat growth and P acquisition.Hence, these studies provided new evidence that role of PSB are extend to multiple effects plant, and thus improving both P acquisition and plant growth. These PSB have great potential to improve plant P nutrition and grain yield with concomitant increase in soil available P for food security with sustainable healthy environment. We expect that novel findings originating from our study will be of great interest for many readers from the fields of microbiology, ecology and environmental sciences.